Effect of Rosuvastatin on Carotid Intima-Media Thickness in Children With Heterozygous Familial Hypercholesterolemia: The CHARON Study (Hypercholesterolemia in Children and Adolescents Taking Rosuvastatin Open Label). Issue 4 (25th July 2017) - Braamskamp, Marjet J.A.M.; Langslet, Gisle; McCrindle, Brian W.; Cassiman, David; Francis, Gordon A.; Gagne, Claude; Gaudet, Daniel; Morrison, Katherine M.; Wiegman, Albert; Turner, Traci; Miller, Elinor; Kusters, D. Meeike; et al.
Abstract : Background: Heterozygous familial hypercholesterolemia (HeFH) is an autosomal dominant disorder leading to premature atherosclerosis. Children with HeFH exhibit early signs of atherosclerosis manifested by increased carotid intima-media thickness (IMT). In this study, we assessed the effect of 2-year treatment with rosuvastatin on carotid IMT in children with HeFH. Methods: Children with HeFH (age, 6–<18 years) and low-density lipoprotein cholesterol >4.9 mmol/L or >4.1 mmol/L in combination with other risk factors received rosuvastatin for 2 years, starting at 5 mg once daily, with uptitration to 10 mg (age, 6–<10 years) or 20 mg (age, 10–<18 years). Carotid IMT was assessed by ultrasonography at baseline and 12 and 24 months in all patients and in age-matched unaffected siblings. Carotid IMT was measured at 3 locations (common carotid artery, carotid bulb, internal carotid artery) in both the left and right carotid arteries. A linear mixed-effects model was used to evaluate differences in carotid IMT between children with HeFH and the unaffected siblings. P values were adjusted for age, sex, carotid artery site, and family relations. Results: At baseline, mean±SD carotid IMT was significantly greater for the 197 children with HeFH compared with the 65 unaffected siblings (0.397±0.049 and 0.377±0.045 mm, respectively; P =0.001). During 2 years of follow-up, the change in carotid IMT was 0.0054 mm/y (95% confidence interval, 0.0030–0.0082) in children with HeFH and 0.0143 mm/y (95% confidence interval, 0.0095–0.0192) in unaffected siblings ( P =0.002). The end-of-study difference in mean carotid IMT between children with HeFH and unaffected siblings after 2 years was no longer significant (0.408±0.043 and 0.402±0.042 mm, respectively; P =0.2). Conclusions: In children with HeFH who were ≥6 years of age, carotid IMT was significantly greater at baseline compared with unaffected siblings. Rosuvastatin treatment for 2 years resulted in significantly less progression of increased carotid IMT in children with HeFH than untreated unaffected siblings. As a result, no difference in carotid IMT could be detected between the 2 groups after 2 years of rosuvastatin. These findings support the value of early initiation of statin treatment for low-density lipoprotein cholesterol reduction in children with HeFH. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01078675.